1970
DOI: 10.4314/ahs.v19i4.47
|View full text |Cite
|
Sign up to set email alerts
|

The effect of myometrial invasion on prognostic factors and survival analysis in endometrial carcinoma

Abstract: Background: We investigated the relationship between myometrial invasion and the prognostic factors on overall and progression free survival in endometrial carcinoma.Methods: 122 cases operated with endometrial cancer were included into the study. Progression-free survival and overall survival were evaluated according to degree of myometrial invasion. We also investigated the relationship between myometrial invasion and prognostic factors. Results: The 5- year progression-free survival rate was 90 % in stage I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

1970
1970
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Another important parameter that effects lymph node metastasis rate and prognosis is myometrial invasion depth. 16 Cirisano et al found lymph node metastasis in 11 cases out of 36 Grade 3 endometrioid carcinoma with tumor invasion more than half of the myometrium while only 1 of 21 cases with less than half myometrial invasion showed lymph node metastasis. 17 In a study by Li et al, it was shown that the risk of metastasis to the pelvic lymph nodes was significantly increased in patients with non-endometrioid type tumor or Grade 3 tumor or with myometrial invasion of more than half.…”
Section: Discussionmentioning
confidence: 97%
“…Another important parameter that effects lymph node metastasis rate and prognosis is myometrial invasion depth. 16 Cirisano et al found lymph node metastasis in 11 cases out of 36 Grade 3 endometrioid carcinoma with tumor invasion more than half of the myometrium while only 1 of 21 cases with less than half myometrial invasion showed lymph node metastasis. 17 In a study by Li et al, it was shown that the risk of metastasis to the pelvic lymph nodes was significantly increased in patients with non-endometrioid type tumor or Grade 3 tumor or with myometrial invasion of more than half.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, European Society for Medical Oncology (ESMO) reported that DMI can be used as a criterion for classification of patients of different risk groups. Dane et al (16) explored the relationship between myometrial invasion and progression-free survival (PFS) or overall survival (OS) in EC. Their findings showed that patients with DMI exhibited a shorter PFS and OS, implying that DMI is an important prognostic indicator and can be used as a determinant of treatment in EC.…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial cancer, approximately 16% at the time of diagnosis, is detected at an advanced stage [16]. According to the surgicalpathological staging, Dane et al [17], found that The 5-year DFS rate was 90% in stage I, 66% in stage II, 32% in stage III and 60% in stage IV and the 5-year OS rate was 95% in stage I, 89% in stage II. 49% in stage III, and 30% in stage IV .…”
Section: Discussionmentioning
confidence: 99%